Pastoraal bidden als samenspraak - Vries, Reijer Jan de (Theologia reformata, 2021)
Presenting the results of a qualitative research on the practice of prayer in pastoral care, this article discusses the questions which most interest ministers in the Protestant Church in the Netherlands. Dialogue - between the pastor and the other, and between the conversation partners and God - is a key issue. The article presents a three-dimensional model of this dialogue and elaborates a theology of pastoral prayer as spiritual fellowship. It then argues that in pastoral care, ministers, with their conversation partners, should pay more attention to the theological quality and the practical significance of dialogue on praying together.